Механізми інтелектуалізації процесів економічного розвитку в умовах глобалізації - Репа, Олександр Іванович; Repa, Oleksandr (ЦНТУ, 2024)
У кваліфікаційній роботі здійснено є поглиблення теоретико-методологічних засад дослідження процесу інтелектуалізації глобального економічного розвитку й обгрунтовано пропозиції щодо розробки стратегічних напрямів включення інтелектуального потенціалу України у світовий інноваційний процес. Комплексний аналіз трансформації об'єктів інтелектуальної власності й інструментів їх регулювання в процесі інтелектуалізації глобалізованої економіки показує, що світовій економічній спільноті необхідно розвивати високотехнологічні, інноваційні галузі й управління інтелектуальною власністю, яке потребує значних інвестицій і відіграє важливу роль у підвищенні національної конкурентоспроможності за рахунок створення й поширення об'єктів ПІВ. Доведено, що ситуація, яка склалася в інноваційній сфері України, робить актуальною розробку державної політики, яка гарантуватиме розширення й відтворення цільової бази інноваційної діяльності з метою впливу на прискорений економічний розвиток країни. Для поліпшення економічної ситуації в Україні, зміщення вектора економічного розвитку із сировинного на інноваційний доцільне залучення національної економіки України до процесу глобальної інтелектуалізації. In qualified work, the immersion of theoretical and methodological ambushes has been completed in tracking the process of intellectualization of global economic development and grounded in propositions for the development of strategic direct inclusion of the intellectual potential of Ukraine in the world innovation process. A comprehensive analysis of the transformation of intellectual power objects and the instruments of their regulation in the process of intellectualization of the globalized economy shows that the Economical productivity requires the development of high-tech, innovative technologies and the management of intellectual power, which will require significant investment and play. important role for advanced National competitiveness for the market is the creation and expansion of IPV facilities. It has been confirmed that the situation that has developed in the innovation sphere of Ukraine requires an urgent development of government policy, which guarantees the expansion and creation of the target base of innovation activity from I intend to accelerate the economic development of the region. To improve the economic situation in Ukraine, to shift the vector of economic development from the economy to an innovative one, to ensure that the national economy of Ukraine is fully prepared before the global process Intellectualization.
Mechanisms of intellectualization of Economic Development Processes in Conditions of Globalization
Keywords: економічний розвиток; інтелектуалізація; глобальна економіка; глобалізація; транснаціоналізація; інтелектуальна власність; інтелектуальний потенціал; інтелектуальні ресурси; economic development; intellectualization; global economy; globalization; transnationalization; intellectual power; intellectual potential; intellectual resources